Auras of Legality - The Jurisdiction and Governance Signature of the International Governance of Official Development Assistance - Airey, Siobhán (Université d'Ottawa / University of Ottawa, 2020)
Official Development Assistance (ODA) or international development aid (defined as the transfer of official financing to promote the development and welfare of developing countries), is a highly influential and politically sensitive area of international relations. Though it is not governed by any international legal agreement, it displays remarkable cohesion across the major Northern donors in its modalities of governance, the coherence in its normative aims and in its institutional reform agenda. In order to understand why, this project focuses on the central, if overlooked, role of the Organisation for Economic Co-operation and Development (OECD) and its Development Assistance Committee (DAC) as the key institutional locus of the international governance of ODA by donors. This project examines the legal nature of the international governance of ODA, tracing and critically analysing the link between the governance of ODA and governance by ODA. It demonstrates how the legal form of the international governance of ODA is central to the reach and effectiveness of the legal and institutional reform agenda promoted via ODA at national and international levels, and to contouring the legal and political subjectivities of donors and aid-recipient states in ways that escape formal legal and democratic recognition. Finding that mainstream legal analytical methods fail to fully capture the legal-juridical quality of the international governance framework of ODA, and the particular role of law therein, I develop a new analytical lens based on the concepts of ‘jurisdiction’ (as juris dictio) and the ‘signature.’ This lens reveals how ODA creates a distinct jurisdiction with its own internal legal logic, where donor and aid-recipient subjectivities and relations of authority are continually constructed and maintained by international governance instruments and practices developed during colonial and imperial governance eras under the League of Nations and Marshall Plan institutions. I demonstrate how this jurisdictional space is augmented by key legal, policy, bureaucratic and technocratic instruments of governance by the OECD and DAC, through patterns of juridification and reiteration.
Keywords: ODA; development aid; law and development; governance of ODA; OECD; OECD DAC; jurisdiction; governance signature; legal form